miR-708-5p promotes fibroblast–like synoviocytes' cell apoptosis and ameliorates rheumatoid arthritis by inhibition of Wnt3a/β-catenin pathway - Wu J (Drug Design, Development and Therapy, 2018)
Jie Wu,1 Wenqiang Fan,1 Ling Ma,1 Xiuqin Geng2 1Department of Rheumatology and Immunology, Central Hospital of Xinxiang, Henan 453000, People’s Republic of China; 2Department of Endocrinology, Central Hospital of Xinxiang, Henan 453000, People’s Republic of China Aim: MicroRNAs (miRNA) are a class of small, highly conserved noncoding RNA molecules, which contain 18–28 nucleotides and are involved in the regulation of gene expression. It has been proved that microRNAs play a very important role in several key cellular processes, such as cell differentiation, cell cycle progression, and apoptosis, as well as in autoimmune disease. One recently identified miRNA, miR-708-5p, has been demonstrated to have profound roles in suppressing oncogenesis in different types of tumors. However, the role of miR-708-5p in rheumatoid arthritis (RA) remains to be fully elucidated. Therefore, in this study, we are aiming to identify the role of miR-708-5p in RA. Methods: The expression level of miR-708-5p in synovial tissues of patients with RA is much lower than in non-RA controls. The effects of miR-708-5p on cell apoptosis, colony formation, and migration in fibroblast-like synoviocytes were assessed in MH7A cells. Results: Results showed that delivery of miR-708-5p mimics into synovial fibroblasts MH7A could induce cell apoptosis and inhibit colony formation and migration. In addition, miR-708-5p mimics significantly inhibit Wnt3a/β-catenin pathway activity both in transcription and protein level, which could be reversed by the addition of R-spondin 1, an activator of Wnt pathway. R-spondin 1 could also reverse the inhibition of cell survival and proliferation, which was induced by miR-708-5p mimics in MH7A. Moreover, injection of miR-708-5p mimics into collagen-induced rat RA model could ameliorate the RA index and decrease Wnt3a/β-catenin expression in rat joint tissues. Conclusion: Therefore, we concluded that miR-708-5p is likely to be involved in RA pathogenesis via inhibition of Wnt3a/β-catenin pathway. Keywords: miR-708-5p, rheumatoid arthritis, cell proliferation, Wnt